Painter of the night. Vol. 1 - Byeonduck (Painter of the Night (Manhwa), 2025)
Na-kyum is a talented artist who excels in painting beautiful gay erotica, though he does so under a pseudonym. Yet recently, he has given up painting, vowing never to create lewd art again. But the notoriously lust-driven nobleman Seungho Yoon didn't get the memo-nor will he accept it-and forces Na-kyum to become his in-house painter, demanding the artist create his erotic works just for Seungho to enjoy. Can Na-kyum endure being Seungho's personal painter of the night or will the late-night activities be too much for him?